Secondary patella resurfacing following primary total knee arthroplasty - Nick D. Clement; Thomas Parsons; Thomas Botfield-Gray; Ricci Plastow; Irrum Afzal; Nardeen Kader; Sarkhell Radha; Deiary F. Kader (The Bone & Joint Journal, 2026)
Aims Our aims were to assess joint-specific outcome (JSO), health-related quality of life (HRQoL), and patient satisfaction following secondary patella resurfacing (SPR), and to define a patient-acceptable symptom state (PASS). Methods This retrospective study was conducted over 16 years (October 2006 to December 2022) and included 182 patients undergoing SPR. Patient demographic details, American Society of Anesthesiologists (ASA) grade, preoperative and postoperative (one year: n = 158 and two years: n = 143) Oxford Knee Score (OKS), EQ-5D, and EQ-VAS scores, as well as postoperative satisfaction, were obtained from a local arthroplasty register. Results There were clinically meaningful and statistically significant (p < 0.001) improvements in the OKS, with a mean change of 6.8 (95% CI 4.7 to 8.9) and 8.1 (95% CI 5.9 to 10.2) points, and in the EQ-5D of 0.174 (95% CI 0.110 to 0.238) and 0.187 (95% CI 0.119 to 0.255) at both one and two years, respectively. There were 126 (79.7%) and 120 (85.7%) satisfied patients at one and two years, respectively. Prior satisfaction with the index total knee arthroplasty (TKA) (one year only: odds ratio (OR) 10.4 (95% CI 3.10 to 34.85); p < 0.001) and increasing time from primary TKA to the SPR (one year: OR 1.37 (for each additional year) (95% CI 1.03 to 1.81); p = 0.028, and two years: OR 2.32 (95% 1.23 to 4.38); p = 0.009) were independently associated with satisfaction. A 2.5-year threshold provided the optimal cutoff for predicting satisfaction, yielding sensitivities of 66.3% and 70.7% and specificities of 67.9% and 68.8% at one and two years, respectively. Thresholds predicted a PASS in the OKS were 20 and 22 at one and two years, respectively. For EQ-5D, the thresholds were 0.500 at both timepoints, and for EQ-VAS were 60 and 63 at one and two years, respectively. At a median follow-up of ten years, no re-revisions were undertaken, and 52 patients (28.1%) died. Conclusion SPR was associated with clinically meaningful improvements in JSO and HRQoL, with high levels of patient satisfaction. Prior satisfaction with the index TKA and longer time to SPR were independently associated with satisfaction, with patients undergoing SPR after 2.5 years more likely to be satisfied. The identification PASS thresholds offer benchmarks for evaluating success. Cite this article: Bone Joint J 2026;108-B(9):1129–1137.